2021
DOI: 10.1371/journal.pone.0247666
|View full text |Cite
|
Sign up to set email alerts
|

A novel micropropagation of Lycium ruthenicum and epigenetic fidelity assessment of three types of micropropagated plants in vitro and ex vitro

Abstract: Lycium ruthenicum is an excellent eco-economic shrub. Numerous researches have been conducted for the function of its fruits but scarcely focused on the somaclonal variation and DNA methylation. An efficient micropropagation protocol from leaves and stems of L. ruthenicum was developed in this study, in which not only the leaf explants but also the stem explants of L. ruthenicum were dedifferentiated and produced adventitious buds/multiple shoots on one type of medium. Notably, the efficient indirect organogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Although no reports were found on the micropropagation of L. schweinfurthii, it is well studied in other species of the Lycium genus. Multiple shoots and adventitious buds of L. ruthenicum were developed in vitro not only from stems but also from leaf explants [9]. Moreover, the best shoot proliferation of L. depressum was achieved at a low concentration of BA (6-benzyl adenine) and rooted in full-strength MS medium (Murashige and Skoog medium) supplemented with IBA (indole-3-butyric acid) with a high survival rate [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although no reports were found on the micropropagation of L. schweinfurthii, it is well studied in other species of the Lycium genus. Multiple shoots and adventitious buds of L. ruthenicum were developed in vitro not only from stems but also from leaf explants [9]. Moreover, the best shoot proliferation of L. depressum was achieved at a low concentration of BA (6-benzyl adenine) and rooted in full-strength MS medium (Murashige and Skoog medium) supplemented with IBA (indole-3-butyric acid) with a high survival rate [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as the presence of bioactive compounds in the explants are thought to be antagonistic to the presence of growth regulators, making it difficult to produce plant embryos. Micropropagation including callus induction and subculture have been carried out to obtain plant buds to be developed into plant seeds [23][24] [25]. The micropropagation carried out in this study has shown potential success in producing good quality seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the treatments includes five replicates. Cultures were maintained in a growth room with a 16-hour photoperiod under fluorescent light at 25 ± 2ºC (Gao et al, 2021;Vijay, Shukla, & Saxena, 2016). Micro solution 5 mL 5 ml 5 mL 5 mL 5 mL 5 mL 3.…”
Section: Preparation Of Media Using Different Carbon Sourcesmentioning
confidence: 99%